Distinct subcellular mechanisms for the enhancement of the surface membrane expression of SK2 channel by its interacting proteins, α‐actinin2 and filamin A. (7th December 2016) - Zhang, Zheng; Ledford, Hannah A.; Park, Seojin; Wang, Wenying; Rafizadeh, Sassan; Kim, Hyo Jeong; Xu, Wilson; Lu, Ling; Lau, Victor C.; Knowlton, Anne A.; Zhang, Xiao‐Dong; Yamoah, Ebenezer N.; et al.
Abstract : Key points: Ion channels are transmembrane proteins that are synthesized within the cells but need to be trafficked to the cell membrane for the channels to function. Small‐conductance, Ca 2+ ‐activated K + channels (SK, KCa 2) are unique subclasses of K + channels that are regulated by Ca 2+ inside the cells; they are expressed in human atrial myocytes and responsible for shaping atrial action potentials. We have previously shown that interacting proteins of SK2 channels are important for channel trafficking to the membrane. Using total internal reflection fluorescence (TIRF) and confocal microscopy, we studied the mechanisms by which the surface membrane localization of SK2 (KCa 2.2) channels is regulated by their interacting proteins. Understanding the mechanisms of SK channel trafficking may provide new insights into the regulation controlling the repolarization of atrial myocytes. Abstract: The normal function of ion channels depends critically on the precise subcellular localization and the number of channel proteins on the cell surface membrane. Small‐conductance, Ca 2+ ‐activated K + channels (SK, KCa 2) are expressed in human atrial myocytes and are responsible for shaping atrial action potentials. Understanding the mechanisms of SK channel trafficking may provide new insights into the regulation controlling the repolarization of atrial myocytes. We have previously demonstrated that the C‐ and N‐termini of SK2 channels interact with the actin‐binding proteins α‐actinin2 and filamin A, respectively. However, the roles of the interacting proteins on SK2 channel trafficking remain incompletely understood. Using total internal reflection fluorescence (TIRF) microscopy, we studied the mechanisms of surface membrane localization of SK2 (KCa 2.2) channels. When SK2 channels were co‐expressed with filamin A or α‐actinin2, the membrane fluorescence intensity of SK2 channels increased significantly. We next tested the effects of primaquine and dynasore on SK2 channels expression. Treatment with primaquine significantly reduced the membrane expression of SK2 channels. In contrast, treatment with dynasore failed to alter the surface membrane expression of SK2 channels. Further investigations using constitutively active or dominant‐negative forms of Rab GTPases provided additional insights into the distinct roles of the two cytoskeletal proteins on the recycling processes of SK2 channels from endosomes. α‐Actinin2 facilitated recycling of SK2 channels from both early and recycling endosomes while filamin A probably aids the recycling of SK2 channels from recycling endosomes. Key points: Ion channels are transmembrane proteins that are synthesized within the cells but need to be trafficked to the cell membrane for the channels to function. Small‐conductance, Ca 2+ ‐activated K + channels (SK, KCa 2) are unique subclasses of K + channels that are regulated by Ca 2+ inside the cells; they are expressed in human atrial myocytes and responsible for shaping atrial action potentials. We have previously shown that interacting proteins of SK2 channels are important for channel trafficking to the membrane. Using total internal reflection fluorescence (TIRF) and confocal microscopy, we studied the mechanisms by which the surface membrane localization of SK2 (KCa 2.2) channels is regulated by their interacting proteins. Understanding the mechanisms of SK channel trafficking may provide new insights into the regulation controlling the repolarization of atrial myocytes.